Decay resistance of thermally-modified Eucalyptus grandis wood at 140 degrees C, 160 degrees C, 180 degrees C, 200 degrees C and 220 degrees C - Calonego, Fred Willians [UNESP]; Durgante Severo, Elias Taylor [UNESP]; Furtado, Edson Luiz [UNESP] (Elsevier B.V., 2010)
The objective of this study was to evaluate the effect of thermal treatment on the biological resistance of Eucalyptus grandis wood to the decay fungus Picnoporus sanguineus. Boards from 5 years and 11 months old E. grandis trees, taken from the stock possessed by the Duratex-SA company, were thermally-modified at 140 degrees C, 160 degrees C, 180 degrees C, 200 degrees C and 220 degrees C in the Laboratory of Wood Drying and Preservation from UNESP, Botucatu, SP, Brazil. Samples of each treatment were treated according to ASTM D-2017 (1994). The experiment tested the accelerated decay caused by the decay fungus P. sanguineus on a system of soil-block wood. The results of thermal treatment showed that an increase of temperature of 180-220 degrees C caused reductions of between 15.7% and 82.4% in the weight loss in the samples from E. grandis incubated with P. sanguineus. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Thermally-modified wood; Eucalyptus grandis; Decay resistance; Picnoporus sanguineus; Soil-block test